Open and laparoscopic transabdominal preperitoneal approach for inguinal hernia: our single institution experience - Thakur, Bhushankumar A.; Mukhamale, Vivek; Deotale, Snehal (International Surgery Journal, 2020)
Background: Trans abdominal preperitoneal (TAPP) a novel approach for inguinal hernia was introduced by Arregui (1991) and Dion in early 1990’s has brought the revolutionary change in the era of hernia surgery over open preperitoneal inguinal hernia repair procedure introduce by Stoppa. Based on this we have done single institution retrospective study of TAPP and open preperitoneal procedure for inguinal hernia. Methods: This study was single institution retrospective study, where we have analyzed the data of 93 male and 7 female patients out of which 50 underwent standard TAPP procedure and 50 patients who underwent open preperitoneal procedure for inguinal hernia, with median 1 year of follow up. Their data analyzed for demographics, surgical site occurrence and short terms recurrence. Results: 100 patients with mean age of 55 years, median ASA of 1, ratio of left: right: bilateral for open 18:30:2 and for laparoscopic 26:20:4. Mean time for surgery was 102.3 min for open and 142.4 mins for TAPP. There was surgical site infection in 3 patients operated by open procedure and 2 patients in TAPP procedure. 4 patients from open procedure group and no one with TAPP group developed seroma which were managed conservatively and resolved at 6 weeks and 8 weeks. One recurrence in TAPP group patient at the 1 week follow. Conclusions: Open preperitoneal repair is hence a technique as effective as laparoscopic hernia repair with a minimal learning curve, ability to be performed under regional anaesthesia and cost effective. It can hence be used to carry out inguinal hernia repairs effectively in rural areas.